'Tablet-in-Syringe': A Novel Dosing Mechanism for Dysphagic Patients Containing Fast-Disintegrating Tablets Fabricated Using Semisolid Extrusion 3D Printing - Pattaraporn Panraksa; Bin Zhang; Pornchai Rachtanapun; Kittisak Jantanasakulwong; Sheng Qi; Pensak Jantrawut (MDPI AG, 2022)
With the ability to fabricate personalized dosage forms and considerably shorter manufacturing time, semisolid extrusion (SSE) 3D printing has rapidly grown in popularity in recent years as a novel, versatile manufacturing method that powers a wide range of applications in the pharmaceutical field. In this work, the feasibility of using SSE 3D printing to fabricate fast-disintegrating tablets (FDTs) that are pre-filled in dosing syringes was evaluated. The novel design approach, 'tablet-in-syringe', was aimed to ease the oral drug administration and improve the dosing accuracy for dysphagic patients. The effect of varying polymer (hydroxypropyl methylcellulose E15) concentrations and printing parameters (e.g., extrusion rate) on dimensional accuracy, physicochemical properties, disintegration time, and content uniformity of 3D-printed FDTs was studied. An overall comparison of results demonstrated that the best FDT formulation among those developed was with a polymer:drug ratio (w/w) of 1:30, printed at extrusion rate of 3.5 μL/s. The diameter of printed filaments of this formulation was observed to be similar to the nozzle diameter (22G), proving that good printing accuracy was achieved. This FDTs also had the fastest disintegration time (0.81 ± 0.14 min) and a drug (phenytoin sodium, as the model drug) content uniformity that met pharmacopeial specifications. Although the flow characteristics of the dissolved formulation still need improvement, our findings suggested that the novel 'tablet-in-syringe' could potentially be considered as a promising fast-disintegrating drug delivery system that can be personalized and manufactured at-or close to-the point of care for dysphagic patients using SSE.